A multicity analysis of daytime Surface Urban Heat Islands in India and the US. (February 2022) - Tetali, Surekha; Baird, Nina; Klima, Kelly
Highlights: In the US, urban land surface temperature (LST) was higher compared to rural LST. Despite urbanization, urban LST in India was lower compared to rural LST. Non-photosynthetic vegetation (NPV) and barren land types influence the results. Built-up indices used here do not differentiate sparse vegetation and built-up surfaces. New methods are needed for quantifying urbanization's impact on LST in India. Abstract: Daytime surface UHI (SUHI) and the factors influencing it across highly populated cities in India and the United States (US) were evaluated. Urban-rural mean land surface temperature (LST) differences (ΔTS ) were calculated and correlated with vegetation and built-up surface densities, quantified using the Normalized Difference Vegetation Index (NDVI) and Index Based Built-Up Index (IBI) respectively. The results from the US show a conventional SUHI phenomenon, and LST decrease with increasing vegetation and decreasing built-up surfaces. However, in India, despite existing urban densities, urban areas are cooler than the rural surroundings. The average LST was higher and NDVI was lower compared to the US, and NDVI and LST correlations were weak. Furthermore, in India, the average IBI values calculated for built-up areas, cropland, and other sparse vegetation land covers were approximately equal. The prevalence of non-photosynthetic vegetation (NPV) and barren soil in India are impacting spectral indices and the correlations. Differences in ΔTS and spectral indices trends between India and US highlight the shortcomings of the indices used in appropriately identifying Indian LULC types and establish the need for localized SUHI research methods that can specifically analyze the impact of urbanization on SUHI in India.